An Overview on Indian Women Novelists in English: Exploring Postcolonial Elements in Indian Women's English Novels (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Presenting an exhaustive political and social change, the novel illuminates starting awarenessof the social, psychological, and social inferiority authorized by colonizers, and presentations struggle ofsubaltern people for ethnic, social, and political independence. Throughout the novel the essayistexpressly and verifiably radiates starts or traces of postcolonial principles to show his enthusiasm fordepicting the fallout of colonization particularly in a time after the liberation. The article, along theselines, aims to investigate the general structure of the novel through postcolonial approach and givesmodels from the novel with respect to the application of some postcolonial elements, for example, lackof clarity, memory, creative mind, personality, essentialism, otherness, inner conflict, nationalism,spaceplace, worlding, diaspora, hybridity, unbelonging, independence… and so on.